2021
DOI: 10.15420/ecr.2020.50
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and Cardiovascular Disease: The Future

Abstract: Despite considerable advances in reducing the global burden of atherosclerotic cardiovascular disease by targeting conventional risk factors, significant residual risk remains, with low-grade inflammation being one of the strongest risk modifiers. Inflammatory processes within the arterial wall or systemic circulation, which are driven in a large part by modified lipoproteins but subsequently trigger a hypercoagulable state, are a hallmark of atherosclerotic cardiovascular disease and, in particular, its clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 93 publications
0
39
0
1
Order By: Relevance
“…Our results agree with previous studies comparing the VLCKD with a hypocaloric diet based on the MedDiet, showing VLCKD to be associated with marked reductions not only in BMI, but also in total body fat and waist circumference, all of which are related to the incidence of CV disease [ 35 , 36 , 37 ]. It has been suggested that nutritional ketosis and DHA supplementation may be added to the greater weight loss as responsible for these beneficial effects [ 15 , 20 , 38 ]. Dietary carbohydrate restriction increases the production of the ketone body ß-hydroxybutyrate, shifting tissue cross-talk from a proinflammatory to an anti-atherogenic environment, addressing the residual inflammatory risk and reducing most of the atherosclerotic CV disease biomarkers [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results agree with previous studies comparing the VLCKD with a hypocaloric diet based on the MedDiet, showing VLCKD to be associated with marked reductions not only in BMI, but also in total body fat and waist circumference, all of which are related to the incidence of CV disease [ 35 , 36 , 37 ]. It has been suggested that nutritional ketosis and DHA supplementation may be added to the greater weight loss as responsible for these beneficial effects [ 15 , 20 , 38 ]. Dietary carbohydrate restriction increases the production of the ketone body ß-hydroxybutyrate, shifting tissue cross-talk from a proinflammatory to an anti-atherogenic environment, addressing the residual inflammatory risk and reducing most of the atherosclerotic CV disease biomarkers [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low-grade inflammation has an important role in T2D and especially in CVD. Inflammatory processes in the arterial wall driven by modified lipoproteins trigger hypercoagulable state [88,89]. The effects of anti-inflammatory drugs to reduce CVD events is likely explained by their interaction with the pathway of the NLRP3 inflammasome to interleukin 1, IL-6, and CRP [90].…”
Section: Mendelian Randomization Studies In Type 2 Diabetes and Cardiovascular Disease: Are There Differences?mentioning
confidence: 99%
“…Since the collected evidence indicates that a state of chronic inflammation has a crucial role in the pathogenesis of obesity-related metabolic dysfunction, where clinical and epidemiological studies describe a clear connection between high levels of proinflammatory cytokines with atherosclerotic lesions that favor cardiovascular events [12], several efforts to integrate interventions targeting lowering the inflammation burden have been carried out [13].…”
Section: Introductionmentioning
confidence: 99%